Optimizing Formalin Detection in Fish Using QCM Sensors with TOMAC Membrane Coatings for Product Quality Monitoring - Muthmainnah Muthmainnah; Khoirul Aini; Imam Tazi; Ninik Chamidah; Kusairi Kusairi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
Detection of formalin in fishery products is a significant concern in the food industry to ensure consumer safety. This study compared the performance of Quartz Crystal Microbalance (QCM) sensors without a membrane and with a Trioctyl methyl ammonium Chloride (TOMAC) membrane coating in detecting formalin in fish samples. The research findings indicate that QCM without a membrane for formalin samples has a lower detection limit of 150 ppm and an upper detection limit of 350 ppm with a sensitivity of 2194.171 Hz/ppm. On the other hand, QCM with a TOMAC membrane coating has a lower detection limit of 400 ppm and an upper detection limit of 550 ppm with a sensitivity of 842.7551 Hz/ppm. Meanwhile, QCM without a membrane for formalin in fish samples has a lower detection limit of 450 ppm and an upper detection limit of 650 ppm with a sensitivity of 15386.38 Hz/ppm. At the same time, QCM with a TOMAC membrane coating for formalin in fish samples has a lower detection limit of 350 ppm and an upper detection limit of 500 ppm with a sensitivity of 23108.9 Hz/ppm. Response time analysis shows that both sensors reach a steady state condition after 12 seconds. This study highlights the importance of selecting appropriate sensors for detecting formalin in fishery products, considering detection limits, sensitivity, and response time as crucial criteria. Thus, these findings can guide the fisheries industry in choosing effective and accurate formalin detection technology.